Preparation of ZrO2-C60 Nanocomposites Using Heat Treatment and Photocatalytic Degradation of Organic Dyes - Hwi Cho, Bum; Bae Ko, Weon (Asian Journal of Chemistry, 2013)
The ZrO2 nanoparticles were synthesized by zirconia solution which is dissolved zirconyl chloride with distilled water and NH4OH solution under microwave irradiation. The ZrO2 and C60 nanocomposites were synthesized in an electric furnace at 700 ºC for 2 h. The heated ZrO2-C60 nanocomposites were characterized by XRD, SEM and TEM. In addition, by using UV-visible spectroscopy, the heated ZrO2-C60 nanocomposites were determinable as a catalyst in the photocatalytic degradation of organic dyes. The photocatalytic effect of the heated ZrO2-C60 nanocomposites was confirmed as being compared with that of ZrO2 nanoparticles after synthesis, heated ZrO2 nanoparticles, unheated ZrO2-C60 nanocomposites in various organic dyes such as methylene blue, methyl orange and rhodamine B under ultraviolet light at 254 nm.